The Impact of Technology on the Modern Art - Krasteva, Mihaela (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2016)
Over the last thirty years, the art enters into a new era of artistic mass production caused by two major developments. The first is the raise of the digital technologies for production of images and objects, while the second is a change in the understanding of what is art, changing the rules by which something is recognized as art or not. Digital technology reshaped completely the way we design and perceive artistic works.
Keywords: digital arts; technology